Impact of stem cell source on allogeneic stem cell transplantation outcome in hematological malignancies - Stamatović Dragana; Balint Bela; Tukić Ljiljana; Elez Marija; Tarabar Olivera; Todorović Milena; Ostojić Gordana; Tatomirović Zeljka; Ljubenov Marika; Marjanović Slobodan; Malešević Milomir (Vojnosanitetski Pregled)
Background/Aim. Peripheral blood (PB) is used more frequently as a source of stem cells (SCs) for allogeneic transplantation. However, the influence of cell source on the clinical outcome of SC transplantation is not yet well established. The aim of this study was to compare the results of PBSC transplantation (PBSCT) with bone marrow transplantation (BMT) on the basis of engraftment, frequency and severity of immediate (mucositis, acute Graft versus Host Disease - aGvHD) and delayed (chronic GvHD - cGvHD) complications, as well as transplant-related mortality (TRM), transfusion needs, relapses and overall survival (OS). Methods. We analyzed 158 patients, women/men ratio 64/94 median age 29 (range 9-57), who underwent allogeneic SC transplantation between 1989 and 2009. All included patients had diseases as follows: acute myeloid leukemia (AML) - 39, acute lymphoblastic leukemia (ALL) - 47, chronic myeloid leukemia (CML) - 32, myelodysplastic syndrome (MDS) - 10, Hodgkin’s lymphoma (HL) - 2, multiple myeloma (MM) - 3, granulocytic sarcoma (GrSa) - 3, severe aplastic anemia (sAA) - 22. The patients underwent transplantations were divided into two groups: BMT group (74 patients) and PBSCT group (84 patients). Each recipient had HLA identical sibling donor. SCs from bone marrow were collected by multiple aspirations of iliac bone and from PB by one “Large Volume Leukapheresis” (after recombinant human granulocyte colony stimulating factor, rHuG-CSF) application (5-12 μg/kgbm, 5 days). Conditioning regimens were applied according to primary disease, GvHD prophylaxis consisted of combination of a cyclosporine A and methotrexate. Results. Engraftment, according to the count of polymorphonuclear and platelets, were significantly (p < 0.001) faster in the PBSCT vs BMT group. The needs for transfusion support were significantly (p < 0.01) higher in the BMT group. Those patients had more frequently oropharingeal mucositis grade 3/4 (33.3% vs 10.0%, p < 0.05). There were no significant differences in the incidence of aGvHD and cGvHD between the two groups. The patients who underwent PBSCT had more frequently extensive cGvHD in comparison with the BMT group (29.1% vs 11.29%, p < 0.05). SC source (SCS) had no significant influence on the TRM (21.62% vs 23.8%, p = 0.64) and the incidence of relapses (21.6% vs 29.7%, p = 0.32). Finally, the patients treated by BMT had a significantly better OS (logrank 2.33, p < 0.05). Conclusion. SCs harvesting from PB resulted in improved cell yield, faster engraftment, as well as in a decrease of immediate transplantation related complications with a reduced treatment cost. Allogeneic PBSCT were associated with more frequent extensive cGvHD, while the influence of SCS in TRM and relapses was not observed. Finally, the longterm OS was better in the patients treated by BMT. To verify impact of SC source on transplantation (PBSCT vs BMT) overall efficacy, more larger randomized clinical studies are needed.